Correction of endotoxin-induced endothelial dysfunction by recombinant erythropoetin and inhibitors of HMG-Co-A-reductase - T. A. Denisyuk; M. V. Pokrovsky; T. G. Pokrovskaya; M. V. Korokin; O. S. Gudyrev; K. M. Reznikov; S. V. Povetkin; A. A. Stepchenko (Кубанский научный медицинский вестник, 2015)
Using the combined use of recombinant erythropoietin «Darbopoetin alpha» (500 mcg / kg) with simvastatin, atorvastatin, rosuvastatin and rosuvastatin nanopartikulirovanny on background modeling sepsis-induced disease, the introduction of strain 603 Staphylococcusaureus shows endotelio- and cardioprotective effects, manifested in preventing the proliferation of QED, adrenoreactivity, maintaining myocardial reserve and the normalization of the values of biochemical markers (Total NO, expression of eNOS, C-reactive protein, IL-6, TNF). Thus, combination therapy found an additive effect of drugs.